A high-efficiency antibacterial ceramic glaze and its preparation process
By using silver-carrying illite with a silicone oil layer on the surface in ceramic glaze as an antibacterial agent, the problem of precipitation of antibacterial agent during sintering is solved, and the efficient antibacterial and antifouling effect of the glaze layer is achieved.
Patent Information
- Application Number
- CN202410854925.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The existing antibacterial ceramic glaze is easy to precipitate during high-temperature sintering, resulting in unsatisfactory antibacterial performance of the glaze layer. At the same time, the ceramic surface is easily contaminated, affecting the aesthetics and use effect.
Silver-carrying illite with a silicone oil layer surface is used as an antibacterial component and mixed with the frit to form an antibacterial glaze component. Through ball milling and aging treatment, the movement of nanosilver is restricted and a hydrophobic effect is formed.
Effectively prevent nano silver from falling out during sintering, maintaining the antibacterial properties of the glaze layer, and achieving good anti-fouling effect through hydrophobic effects.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic glazes, and in particular to a high-efficiency antibacterial ceramic glaze and a preparation process thereof. Background Art
[0002] Ceramics is a product with a special shape that is made of natural clay as the main raw material through mixing, molding, and sintering. With the development of science and technology, functional ceramic products have gradually entered people's daily lives. Ceramic glaze is a key component of ceramic products. It is mainly made by finely grinding mineral raw materials to form a slurry, and then treating it at high temperature so that it can be covered on the surface of ceramics, thereby improving the gloss of ceramic products. Therefore, if you want to realize the production of functional ceramic products, you can start with the modification of ceramic glaze.
[0003] Antibacterial ceramic glaze is a special ceramic glaze. By adding antibacterial agents to the glaze, the surface of the ceramic product has antibacterial function. Common antibacterial agents include inorganic silver ion antibacterial agents, inorganic zinc ion antibacterial agents, and nano-scale metal oxides. These antibacterial agents destroy the cell membrane of bacteria by physical or chemical means, inhibiting the growth and reproduction of bacteria, thereby achieving the antibacterial effect. However, these antibacterial agents will gradually precipitate and ablate during the high-temperature sintering process, resulting in the glaze layer formed by sintering actually showing unsatisfactory antibacterial properties. In addition, in actual use, a large number of ceramics will inevitably come into contact with sewage, tea, etc., which may leave dirt on the surface of the ceramics, which will not only affect the appearance, but may also become a hotbed for bacterial incubation, which will have a negative impact on the use of ceramic products.
[0004] Based on this, the present invention provides a ceramic glaze with antibacterial and antifouling functions, which can meet the needs of functional ceramic products. Summary of the invention
[0005] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a high-efficiency antibacterial ceramic glaze and a preparation process thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A high-efficiency antibacterial ceramic glaze, composed of a ceramic base glaze component and an antibacterial glaze component; the antibacterial glaze component includes the following raw materials in parts by weight:
[0008] 40-60 parts of frit;
[0009] 5-15 parts of antibacterial component;
[0010] The antibacterial component is silver-loaded illite with a silicone oil layer coated on the surface.
[0011] As a further embodiment of the present invention, the preparation method of the antibacterial glaze component is as follows:
[0012] Add the frit and antibacterial components to the ball mill in sequence, and grind until the material can pass through the 80-100 mesh screen. Add water to the filtered mixture to adjust the specific gravity to 1.2-1.5g / cm 3 , the antibacterial component can be obtained.
[0013] As a further embodiment of the present invention, the preparation method of the antibacterial component is as follows:
[0014] Step 1, stirring and mixing the pretreated illite and the silver nitrate solution to form a mixed solution, ultrasonically treating the mixed solution at an ultrasonic frequency of 80-100 kHz for 1-2 hours, irradiating the mixed solution with a 365 nm ultraviolet lamp for 10-30 minutes, discharging the mixed solution, and obtaining an illite composite material;
[0015] Step 2: adding the silver ammonia solution to a glucose solution with a concentration of 0.1-0.3 mol / L, stirring to form a mixed solution, then immersing the illite composite in the mixed solution, controlling the temperature at 80-90° C., keeping the temperature for 30-60 minutes and then taking it out to obtain silver-loaded illite;
[0016] Step 3: Disperse the silver-loaded illite in ethanol with a volume fraction of 70-75%, then add the terminal amino silicone oil to the dispersion, stir and mix at a speed of 300-500r / min for 40-60min, then add the terminal epoxy silicone oil, after the addition, heat to 60-70°C, keep stirring for 3-6h, cool and discharge, and the antibacterial component can be obtained.
[0017] In the above technical scheme, illite is first pre-treated by calcination and acid treatment to fully expose the pores of the illite. Under ultrasonic oscillation conditions, silver ions will break through the pore port barrier and enter the pores of the illite. After ultraviolet irradiation, these silver ions are gradually loaded on the surface and pores of the illite in the form of seeds. In the silver ammonia solution, the silver seeds gradually grow and gradually become nanosilver under the reducing action of glucose. Then, the nanosilver is loaded in the pores of the illite to obtain silver-loaded illite. In step three, since the surface of the illite carries a negative charge, it can attract the terminal amino silicone oil under the classical action, and the terminal amino silicone oil is adsorbed on the surface of the silver-loaded illite. Then, the terminal epoxy silicone oil is used as a bridging agent to coat the surface of the silver-loaded illite with a silicone oil layer having a cross-linked structure to obtain an antibacterial component.
[0018] Since the surface of the antibacterial component is coated with a silicone oil layer, the presence of these silicone oil layers can limit the movement of nanosilver in the pores of illite. Therefore, during the subsequent ball milling and grinding process, the nanosilver will not easily escape from the pores of the illite.
[0019] As a further solution of the present invention, in step 1, the pretreatment method of illite is as follows:
[0020] Place the illite in a muffle furnace, calcine it at 400-500°C for 1-3 hours, take it out, wait for it to cool, immerse it in a hydrochloric acid solution at 50-60°C for 1-3 hours, take it out, and wash it until it is neutral.
[0021] As a further embodiment of the present invention, in step 1, the concentration of the silver nitrate solution is 0.05-0.1 mol / L.
[0022] As a further embodiment of the present invention, in step three, the weight average molecular weight of the amino-terminated silicone oil is 1000-2000; the weight average molecular weight of the epoxy-terminated silicone oil is 1000-2000; and the mass ratio of the amino-terminated silicone oil to the epoxy-terminated silicone oil is 1:1.
[0023] As a further embodiment of the present invention, the ceramic base glaze component comprises the following raw materials in parts by weight:
[0024] Potassium feldspar 20-35 parts, dolomite 4-5 parts, calcite 8-10 parts, wollastonite 12-15 parts, glass powder 5-15 parts, calcined talc 2.5-5 parts, boron oxide 4-6 parts, quartz 20-30 parts, aluminum oxide 3-5 parts, borax 4-6 parts;
[0025] The preparation method of the ceramic basic glaze component is as follows:
[0026] Step ①, weigh the above raw materials according to weight, grind them into 10-30 mesh, and place them in a sintering furnace, control the temperature in the sintering furnace to 1500-1600°C, sinter for 2-4 hours, discharge the materials, quench with water, and form a sintered material;
[0027] Step ②, place the sintered material in a ball mill, control the mass ratio of sintered material, ball, and water to be 1:2-2.5:0.5-0.8, wet ball mill for 10-12 hours, discharge the material, and add water to adjust the specific gravity of the material to 1.7-1.8g / cm 3 , the ceramic basic glaze components can be obtained.
[0028] A preparation process of a highly effective antibacterial ceramic glaze comprises the following steps:
[0029] The first step is to evenly mix the ceramic base glaze component and the antibacterial glaze component, add them into a grinder, and grind them until the sieve residue of the 10,000-hole sieve is less than 0.05%, so as to form a mixed glaze;
[0030] Step 2: Add sodium humate to the mixed glaze, stir evenly, and then age at 30-40°C for 10-20 days to form an aged glaze;
[0031] The third step is to add water to the aged glaze and adjust the specific gravity to 1.5-1.65g / cm 3 , then add the binder, stir evenly mechanically, let it stand to degas, and then you can get the ceramic glaze.
[0032] As a further solution of the present invention, in the first step, the mass ratio of the ceramic base glaze component to the antibacterial glaze component is 1:0.12-0.18.
[0033] As a further solution of the present invention, in the third step, the adhesive is at least one of polyvinyl alcohol, sodium carboxymethyl cellulose or methyl cellulose.
[0034] Beneficial effects of the present invention:
[0035] The present invention forms an antibacterial component by limiting nano-silver in the pores of illite, and coating the surface of illite with a silicone oil layer, and then grinding and mixing with a frit to form an antibacterial glaze component. Due to the presence of the silicone oil layer, the surface of the antibacterial component has higher lubricity, and can avoid the pore structure from being destroyed in large quantities during the grinding process with the frit, resulting in the outflow of nano-silver in the pores, causing the problem of weakened antibacterial performance. In addition, during the high-temperature firing process of the ceramic glaze, organic matter in the silicone oil layer of the cross-linked structure is ablated to form silica sols, which have extremely low surface energy and can make the glaze layer show a highly hydrophobic effect, thereby making the glaze layer show a good antifouling effect. At the same time, the pore structure of illite can play a good protective role on nano-silver, and the ablation phenomenon of nano-silver during the high-temperature sintering process of the glaze can be avoided. Moreover, after the silicone oil layer is ablated, the pore structure is released, thereby realizing the slow release of nano-silver, so that the glaze layer shows excellent antibacterial performance.
[0036] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The antibacterial components in the following examples and comparative examples were prepared by the following method:
[0039] Step 1: Place illite with an average particle size of 5 μm in a muffle furnace, calcine it at 450°C for 2 hours, take it out, and after cooling it, immerse it in a 2 mol / L hydrochloric acid solution at 60°C for 2 hours, take it out, and wash it until it is neutral.
[0040] Step 2: 5 g of the pretreated illite was stirred and mixed with 100 mL of a 0.05 mol / L silver nitrate solution to form a mixed solution, and then the mixed solution was ultrasonically treated at an ultrasonic frequency of 100 kHz for 2 h, and then the mixed solution was irradiated with a 365 nm ultraviolet lamp for 20 min, and the material was discharged to obtain an illite composite material;
[0041] Step 3: Add 20 mL of 0.3 mol / L silver ammonia solution to 10 mL of 0.2 mol / L glucose solution, stir to form a mixed solution, then immerse 1 g of illite composite in the mixed solution, control the temperature at 80°C, keep warm for 40 minutes and then take out to obtain silver-loaded illite;
[0042] Step 4: Disperse 1.5 g of silver-loaded illite in 75% ethanol by volume, then add 12.5 g of terminal amino silicone oil with a weight average molecular weight of 2000 to the dispersion, stir and mix at a speed of 400 r / min for 40 minutes, then add 12.5 g of terminal epoxy silicone oil with a weight average molecular weight of 2000, after the addition is completed, heat to 65°C, stir and keep warm for 5 hours, cool and discharge the material, and the antibacterial component can be obtained.
[0043] Example 1
[0044] 1. Preparation of antibacterial glaze components
[0045] Weigh 40 parts of 809 frit and 5 parts of antibacterial component by weight, add them into the ball mill in sequence, and ball mill until the material can pass through a 100-mesh sieve. Add water to the filtered mixture to adjust the specific gravity to 1.2 g / cm 3 , the antibacterial component can be obtained.
[0046] 2. Preparation of ceramic basic glaze components
[0047] Step ①, weigh 20 parts of potassium feldspar, 4 parts of dolomite, 8 parts of calcite, 12 parts of wollastonite, 5 parts of glass powder, 2.5 parts of calcined talc, 4 parts of boron oxide, 20 parts of quartz, 3 parts of aluminum oxide, and 4 parts of borax according to weight parts, grind them into 10 meshes, and place them in a sintering furnace, control the temperature in the sintering furnace to 1500° C., sinter for 4 hours, discharge the materials, and quench them in water to form a sintered material;
[0048] Step ②, place the sintered material in a ball mill, control the mass ratio of sintered material, ball and water to be 1:2:0.5, wet ball mill for 10 hours, discharge the material, add water to adjust the specific gravity of the material to 1.7g / cm3 , the ceramic basic glaze components can be obtained.
[0049] 3. Preparation of High-efficiency Antibacterial Ceramic Glaze
[0050] The first step is to evenly mix the ceramic base glaze component and the antibacterial glaze component in a mass ratio of 1:0.12, add the mixture into a grinder, and grind until the residue on the 10,000-hole sieve is less than 0.05%, thereby forming a mixed glaze;
[0051] Step 2: adding sodium humate to the mixed glaze, controlling the amount of sodium humate added to be 0.15% of the solid mass in the mixed glaze, stirring evenly, and aging at 30° C. for 20 days to form an aged glaze;
[0052] The third step is to add water to the aged glaze and adjust the specific gravity to 1.5g / cm 3 Then, polyvinyl alcohol is added, and the amount of polyvinyl alcohol added is controlled to be 0.05% of the solid mass in the aged glaze. After mechanical stirring, the mixture is allowed to stand and degas, and the ceramic glaze can be obtained.
[0053] Example 2
[0054] 1. Preparation of antibacterial glaze components
[0055] Weigh 50 parts of 809 frit and 12 parts of antibacterial components by weight, add them into the ball mill in sequence, and ball mill until the material can pass through a 100-mesh sieve. Add water to the filtered mixture to adjust the specific gravity to 1.4 g / cm 3 , the antibacterial component can be obtained.
[0056] 2. Preparation of ceramic basic glaze components
[0057] Step ①, weigh 30 parts of potassium feldspar, 4.5 parts of dolomite, 10 parts of calcite, 13 parts of wollastonite, 10 parts of glass powder, 3 parts of calcined talc, 5 parts of boron oxide, 25 parts of quartz, 4 parts of aluminum oxide, and 5 parts of borax according to weight parts, grind them into 30 meshes, and place them in a sintering furnace, control the temperature in the sintering furnace to 1550° C., sinter for 3 hours, discharge the materials, and quench them in water to form a sintered material;
[0058] Step ②, place the sintered material in a ball mill, control the mass ratio of sintered material, ball and water to be 1:2.5:0.6, wet ball mill for 12 hours, discharge the material, add water to adjust the specific gravity of the material to 1.8g / cm 3 , the ceramic basic glaze components can be obtained.
[0059] 3. Preparation of High-efficiency Antibacterial Ceramic Glaze
[0060] The first step is to evenly mix the ceramic base glaze component and the antibacterial glaze component in a mass ratio of 1:0.16, add the mixture into a grinder, and grind until the residue on the 10,000-hole sieve is less than 0.05%, thereby forming a mixed glaze;
[0061] Step 2: adding sodium humate to the mixed glaze, controlling the amount of sodium humate added to be 0.15% of the solid mass in the mixed glaze, stirring evenly, and aging at 40° C. for 15 days to form an aged glaze;
[0062] The third step is to add water to the aged glaze and adjust the specific gravity to 1.6g / cm 3 Then, add sodium carboxymethyl cellulose, and control the amount of sodium carboxymethyl cellulose added to be 0.05% of the solid mass in the aged glaze. After mechanical stirring, let it stand for degassing to obtain the ceramic glaze.
[0063] Example 3
[0064] 1. Preparation of antibacterial glaze components
[0065] Weigh 60 parts of 809 frit and 15 parts of antibacterial component by weight, add them into the ball mill in sequence, and ball mill until the material can pass through a 100-mesh sieve. Add water to the filtered mixture to adjust the specific gravity to 1.5 g / cm 3 , the antibacterial component can be obtained.
[0066] 2. Preparation of ceramic basic glaze components
[0067] Step ①, weigh 35 parts of potassium feldspar, 5 parts of dolomite, 10 parts of calcite, 15 parts of wollastonite, 15 parts of glass powder, 5 parts of calcined talc, 6 parts of boron oxide, 30 parts of quartz, 5 parts of aluminum oxide, and 6 parts of borax according to weight parts, grind them to 30 mesh, and place them in a sintering furnace, control the temperature in the sintering furnace to 1600° C., sinter for 2 hours, discharge the materials, and quench them in water to form a sintered material;
[0068] Step ②, place the sintered material in a ball mill, control the mass ratio of sintered material, ball and water to be 1:2.5:0.8, wet ball mill for 12 hours, discharge the material, add water to adjust the specific gravity of the material to 1.8g / cm 3 , the ceramic basic glaze components can be obtained.
[0069] 3. Preparation of High-efficiency Antibacterial Ceramic Glaze
[0070] The first step is to evenly mix the ceramic base glaze component and the antibacterial glaze component in a mass ratio of 1:0.18, add the mixture into a grinder, and grind until the residue on the 10,000-hole sieve is less than 0.05%, thereby forming a mixed glaze;
[0071] Step 2: adding sodium humate to the mixed glaze, controlling the amount of sodium humate added to be 0.15% of the solid mass in the mixed glaze, stirring evenly, and aging at 40° C. for 20 days to form an aged glaze;
[0072] The third step is to add water to the aged glaze and adjust the specific gravity to 1.65g / cm 3 Then, add sodium carboxymethyl cellulose, and control the amount of sodium carboxymethyl cellulose added to be 0.05% of the solid mass in the aged glaze. After mechanical stirring, let it stand for degassing to obtain the ceramic glaze.
[0073] Comparative Example 1
[0074] The high-efficiency antibacterial ceramic glaze in this comparative example is directly ground using the ceramic basic glaze components in Example 2 until the sieve residue on the 10,000-hole sieve is less than 0.05%. 0.3% of the solid mass of nano-silver oxide in the mixed glaze is added to the mixed glaze as an antibacterial agent, and the other preparation steps are the same as those in Example 2.
[0075] Test Case
[0076] Take a ceramic blank with a specification of 10cm×10cm×5mm, place it in a sintering furnace, take it out after sintering at 650℃ for 3h to form a blank, and respectively immerse the blank in the ceramic glazes in Examples 1 to 3 of the present invention and Comparative Example 1. Through multiple immersions, the thickness of the glaze layer is controlled to 0.1mm. After the impregnation is completed, place it in a kiln for firing, control the temperature to 1350℃, take it out after firing for 6h, and after cooling, form a test sample.
[0077] A. According to the standard JC / T 897-2014, Staphylococcus aureus was used as the test strain to conduct relevant performance tests, and the results are recorded in the following table:
[0078] Example 1 Example 2 Example 3 Comparative Example 1 Antibacterial rate / % >99.9 >99.9 >99.9 76.4
[0079] B. Use MIT-60 gloss meter to measure the glaze gloss of the sample to be tested, with an incident angle of 60°; use TC-A3 automatic contact angle measuring instrument to test the glaze water contact angle of the sample to be tested, and the results are recorded in the following table:
[0080] Example 1 Example 2 Example 3 Comparative Example 1 Glossiness / % 81.2 81.2 80.9 80.1 Water contact angle / ° 151.1 151.4 150.7 117.0
[0081] The above test results show that the ceramic glaze made by adding antibacterial glaze components has excellent antibacterial properties, and the water contact angle is higher than 150°, and the surface is super hydrophobic, so it has a good antifouling effect. The ceramic glaze supported by silver oxide instead of antibacterial glaze components undergoes silver ablation and precipitation during high-temperature firing, which greatly weakens the antibacterial effect. Moreover, since silica sol cannot be produced after sintering, the hydrophobic effect is poor and the antifouling effect is average.
[0082] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A highly effective antibacterial ceramic glaze, characterized in that: The invention is composed of a ceramic basic glaze component and an antibacterial glaze component; the antibacterial glaze component comprises the following raw materials in parts by weight: 40-60 parts of frit; 5-15 parts of antibacterial component; The antibacterial component is silver-loaded illite with a silicone oil layer coated on the surface; The preparation method of the antibacterial component is as follows: Step 1, stirring and mixing the pretreated illite and the silver nitrate solution to form a mixed solution, ultrasonically treating the mixed solution at an ultrasonic frequency of 80-100 kHz for 1-2 hours, irradiating the mixed solution with a 365 nm ultraviolet lamp for 10-30 minutes, discharging the mixed solution, and obtaining an illite composite material; Step 2: adding the silver ammonia solution to a glucose solution with a concentration of 0.1-0.3 mol / L, stirring to form a mixed solution, then immersing the illite composite in the mixed solution, controlling the temperature at 80-90° C., keeping the temperature for 30-60 minutes and then taking it out to obtain silver-loaded illite; Step 3, dispersing the silver-loaded illite in ethanol with a volume fraction of 70-75%, then adding the amino-terminated silicone oil, stirring and mixing at a speed of 300-500 r / min for 40-60 minutes, and then adding the epoxy-terminated silicone oil. After the addition is completed, the temperature is raised to 60-70°C, and after stirring for 3-6 hours, the temperature is lowered and the material is discharged to obtain the antibacterial component; The preparation method of the antibacterial glaze component is as follows: Add the frit and the antibacterial component to the ball mill in sequence, and ball-mill until the material can pass through an 80-100 mesh sieve. Add water to the filtered mixture and adjust the specific gravity to 1.2-1.5 g / cm3 to obtain the antibacterial glaze component. During the high-temperature firing process of the ceramic glaze, organic matter in the cross-linked silicone oil layer formed by the amino-terminated silicone oil and the epoxy-terminated silicone oil is ablated to form silica sols. These silica sols have extremely low surface energy and can make the glaze layer formed by the ablation of the glaze show a highly hydrophobic effect.
2. The high-efficiency antibacterial ceramic glaze according to claim 1, characterized in that: In step 1, the illite pretreatment method is as follows: Place the illite in a muffle furnace, calcine it at 400-500°C for 1-3 hours, take it out, wait for it to cool, immerse it in a hydrochloric acid solution at 50-60°C for 1-3 hours, take it out, and wash it until it is neutral.
3. The high-efficiency antibacterial ceramic glaze according to claim 1, characterized in that: In step 1, the concentration of the silver nitrate solution is 0.05-0.1 mol / L.
4. The high-efficiency antibacterial ceramic glaze according to claim 1, characterized in that: In step three, the weight average molecular weight of the amino-terminated silicone oil is 1000-2000; the weight average molecular weight of the epoxy-terminated silicone oil is 1000-2000; and the mass ratio of the amino-terminated silicone oil to the epoxy-terminated silicone oil is 1:
1.
5. The high-efficiency antibacterial ceramic glaze according to claim 1, characterized in that: The ceramic base glaze component includes the following raw materials in parts by weight: Potassium feldspar 20-35 parts, dolomite 4-5 parts, calcite 8-10 parts, wollastonite 12-15 parts, glass powder 5-15 parts, calcined talc 2.5-5 parts, boron oxide 4-6 parts, quartz 20-30 parts, aluminum oxide 3-5 parts, borax 4-6 parts; The preparation method of the ceramic basic glaze component is as follows: Step ①, weigh the above raw materials according to weight, grind them into 10-30 mesh, and place them in a sintering furnace, control the temperature in the sintering furnace to 1500-1600°C, sinter for 2-4 hours, discharge the materials, quench with water, and form a sintered material; Step ②, place the sintered material in a ball mill, control the mass ratio of sintered material, ball and water to be 1:2-2.5:0.5-0.8, wet ball mill for 10-12 hours, discharge the material, add water to adjust the specific gravity of the material to 1.7-1.8g / cm3, and obtain the ceramic basic glaze component.
6. A process for preparing a highly effective antibacterial ceramic glaze as claimed in claim 1, characterized in that: The following steps are involved: The first step is to evenly mix the ceramic base glaze component and the antibacterial glaze component, add them into a grinder, and grind them until the sieve residue of the 10,000-hole sieve is less than 0.05%, so as to form a mixed glaze; Step 2: Add sodium humate to the mixed glaze, stir evenly, and then age at 30-40°C for 10-20 days to form an aged glaze; The third step is to add water to the aged glaze to adjust the specific gravity to 1.5-1.65g / cm3, then add the binder, stir evenly mechanically, let it stand to degas, and then the ceramic glaze can be obtained.
7. The process for preparing a highly effective antibacterial ceramic glaze according to claim 6, characterized in that: In the first step, the mass ratio of the ceramic base glaze component to the antibacterial glaze component is 1:0.12-0.
18.
8. The process for preparing a highly effective antibacterial ceramic glaze according to claim 6, characterized in that: In the third step, the binder is at least one of polyvinyl alcohol, sodium carboxymethyl cellulose or methyl cellulose.
Citation Information
Patent Citations
Modified illite-loaded nano silver antibacterial material and preparation method thereof
CN107159166A
Slow-release chlorine dioxide composite antibacterial material and preparation method of composite antibacterial material
CN111528223A
Antibacterial ceramic tile and preparation method thereof
CN115073003A
Nano antibacterial ceramic glaze and preparation method thereof
CN119038877A